2021
DOI: 10.1088/1741-2552/ac1ab3
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning multimodal fNIRS and EEG signals for bimanual grip force decoding

Abstract: ObjectiveNon-invasive brain-machine interfaces (BMIs) offer an alternative, safe and accessible way to interact with the environment. To enable meaningful and stable physical interactions, BMIs need to decode forces. Although previously addressed in the unimanual case, controlling forces from both hands would enable BMI-users to perform a greater range of interactions. We here investigate the decoding of hand-specific forces.Approach We maximise cortical information by using electroencephalography (EEG) and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…Zheng et al [41] explored the functional connectivity between multiple cortical areas during grip force tracking tasks at 25%, 50%, and 75% of MVC with fNIRS and found the functional connectivity between the left prefrontal cortex and the left sensorimotor cortex and between the right prefrontal cortex and the right sensorimotor cortex strengthened with a higher grip force level. Ortega et al [42] have revealed traces of the brain activity being modulated by the level of hand-specific forces (10, 17.5, or 25% of MVC) using EEG and fNIRS and reconstructed bimanual force trajectories. Andrushko et al [43] found increases in right-handgrip force resulted in greater ipsilateral sensorimotor activation and greater functional connectivity between hemispheres within the sensorimotor network with 25%, 50%, and 75% of MVC.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al [41] explored the functional connectivity between multiple cortical areas during grip force tracking tasks at 25%, 50%, and 75% of MVC with fNIRS and found the functional connectivity between the left prefrontal cortex and the left sensorimotor cortex and between the right prefrontal cortex and the right sensorimotor cortex strengthened with a higher grip force level. Ortega et al [42] have revealed traces of the brain activity being modulated by the level of hand-specific forces (10, 17.5, or 25% of MVC) using EEG and fNIRS and reconstructed bimanual force trajectories. Andrushko et al [43] found increases in right-handgrip force resulted in greater ipsilateral sensorimotor activation and greater functional connectivity between hemispheres within the sensorimotor network with 25%, 50%, and 75% of MVC.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in an average fraction of variance accounted for of 55% when reconstructing the discrete grip force profiles, demonstrating that not only can the DL techniques distinguish which hand was performing a motor task, they also display progress toward using fNIRS and EEG signals to determine the amount of force exerted during that motor task. Ortega and Faisal 66 then attempted to use this architecture to determine force onset and which hand was providing more force. This resulted in a force onset detection of 85% but only a hand disentanglement accuracy of 53%, showing that there is still progress to be made toward the complex decoding and reconstruction of motor activities.…”
Section: Applications In Fnirsmentioning
confidence: 99%
“…In the literature on classification problems within cognitive science, DL architectures, such as Multilayer Perceptron (MLP), Convolutional Neural Network (CNN), Long Short-Term Memory (LSTM), and their hybrid forms, are commonly used for both EEG and fNIRS BCI problems. Additionally, most studies rely on the k-fold cross-validation metric for evaluation [20,33,41,44].…”
Section: Introductionmentioning
confidence: 99%